A dual coil induction heating machine for jewelry factories developed by electromagnetic analysis - Sorathorn Pattanapichai; Thodsaphon Jansaengsuk; Jatuporn Thongsri (Journal of Advanced Joining Processes, 2023)
An induction heating machine (IHM) generates magnetic flux density (B) and high temperature for combining precious metals as products in a jewelry factory. Since factories require new generation IHMs for increased productivity and cost savings, a dual coil IHM development approach is presented here to replace conventional, single-coil IHM using electromagnetic analysis (EMA). First, the experiments and the EMA investigated B generated by a conventional one using the factory operating condition. Both agreed, confirming the methodology and reliability of the EMA, which was analyzed to determine Bp. The Bp represents a B property for the new dual coil IHM to be expected to generate a comparable signal to the single coil. Then, in development, two novel designs of dual coil IHM (series and parallel) were investigated based on current flow circuits. For these designs, Bp was investigated using the EMA. As expected, the EMA results showed that both coils generated a different Bp, which was unfortunately incompatible with the conventional IHM and thus was inappropriate in actual use. However, the series dual coil showed better applicability since it generated B higher than the parallel coil under the same operating conditions. Next, the EMA was applied to determine the Bp of the series dual coil by varying the applied current (I), frequency (f), number of coil turns (N), and distance between coils (d). Finally, the EMA results revealed two options of the series dual coil with the optimum I, f, N, and d generating Bp comparable to the conventional IHM, as intended, achieving the factory's need with two times the productivity.
Keywords: Induction Heating and Inverter Technology; Electric Motor Design and Analysis; Magnetic Properties and Applications